Regime-switching dynamics of exchange rate movements and stock market performance in Nigeria: A Markov-switching VAR approach - Kurfi, Jamilu Amadi; Zarma, Musa Mustapha; Akanegbu, Benedict (Edelweiss Applied Science and Technology, 2026)
This study investigates the regime-dependent effects of exchange rate movements on stock market performance in Nigeria from 1999Q1 to 2023Q4 using a Markov-Switching Vector Autoregression (MS-VAR) framework. The primary objective is to assess how the relationship between the Real Effective Exchange Rate (REER) and the All-Share Index (ASI) varies across different economic regimes. Preliminary analysis revealed a strong positive correlation (0.796) between REER and ASI, with both series being non-stationary at levels but integrated of order one. The MS-VAR model identified two distinct regimes: Regime 1, a stable state with 94.5% persistence representing normal economic conditions, and Regime 2, a volatile state representing short-term economic stress. In Regime 1, exchange rate movements positively influenced stock market performance (coefficient = 0.056), while in Regime 2, the impact was stronger (coefficient = 0.079). Impulse response analysis indicated that exchange rate shocks exert their highest effect on the stock market in the short term (0.047), diminishing to 0.022 in the long term. The findings underscore the importance of considering economic regimes in understanding the exchange rate–stock market nexus, offering insights for policymakers, investors, and financial analysts in managing market risks.